Synthesis and Characterization of Hybrid Ni0.5Zn0.5Fe2O4@SiO2/chitosan - Santos,Polyana Tarciana Araújo dos (2017)
In this work we evaluate the use of silane agent 3-aminopropyltrimethoxysilane and biopolymer chitosan to functionalize ferrites Ni0.5Zn0.5Fe2O4 using the solvent evaporation method aiming at obtaining hybrid material Ni0.5Zn0.5Fe2O4@SiO2/chitosan for use as a biosensor. The nanoparticles before and after the functionalization showed the major phase Ni0.5Zn0.5Fe2O4. The FTIR spectra showed absorption bands characteristic of CO, axial deformation of CN and SiO band from the silane agent which proved functionalization. The functionalization of ferrite Ni0.5Zn0.5Fe2O4 with chitosan caused a 36.36% reduction in saturation magnetization as compared with ferrite synthesized, however it maintained the ferrimagnetic characteristic indicating to be a promising material for the use in biotechnological applications as for example in magnetic biosensors.